One-dimensional quantum antiferromagnetism in the p -orbital CsO2 compound revealed by electron paramagnetic resonance - Knaflic, Tilen; Klanjsek, Martin; Sans, Annette; Adler, Peter; Jansen, Martin; Felser, Claudia; Arcon, Denis (Physical Review B - Condensed Matter and Materials Physics, 2015)
Recently, it was proposed that the orbital ordering of πx,y∗ molecular orbitals in the superoxide CsO2 compound leads to the formation of spin-1/2 chains below the structural phase transition occurring at Ts1=61 K on cooling. Here we report a detailed X-band electron paramagnetic resonance (EPR) study of this phase in CsO2 powder. The EPR signal appears as a broad line below Ts1, which is replaced by the antiferromagnetic resonance below the Néel temperature TN=8.3 K. The temperature dependence of the EPR linewidth between Ts1 and TN agrees with the predictions for the one-dimensional Heisenberg antiferromagnetic chain of S=1/2 spins in the presence of symmetric anisotropic exchange interaction. Complementary analysis of the EPR line shape, linewidth, and the signal intensity within the Tomonaga-Luttinger liquid (TLL) framework allows for a determination of the TLL exponent K=0.48. Present EPR data thus fully comply with the quantum antiferromagnetic state of spin-1/2 chains in the orbitally ordered phase of CsO2, which is therefore a unique p-orbital system where such a state could be studied.
CRIS-Team Scopus Importer:2023-03-20